Peripheral and local predictive immune signatures identified in a phase II trial of ipilimumab with carboplatin/paclitaxel in unresectable stage III or stage IV melanoma. Issue 1 (21st November 2017) - Jamal, Rahima; Lapointe, Réjean; Cocolakis, Eftihia; Thébault, Paméla; Kazemi, Shirin; Friedmann, Jennifer E.; Dionne, Jeanne; Cailhier, Jean-François; Bélanger, Karl; Ayoub, Jean-Pierre; Le, Huy; Lambert, Caroline; et al.
Abstract : Background: Checkpoint blockade with ipilimumab provides long-term survival to a significant proportion of patients with metastatic melanoma. New approaches to increase survival and to predict which patients will benefit from treatment are needed. This phase II trial combined ipilimumab with carboplatin/paclitaxel (CP) to assess its safety, efficacy, and to search for peripheral and tumor-based predictive biomarkers. Methods: Thirty patients with untreated unresectable/metastatic melanoma were treated with ipilimumab and CP. Adverse events (AEs) were monitored and response to treatment was evaluated. Tumor tissue and peripheral blood were collected at specified time points to characterize tumor immune markers by immunohistochemistry and systemic immune activity by multiplex assays and flow cytometry. Results: Eighty three percent of patients received all 5 cycles of CP and 93% completed ipilimumab induction. Serious AEs occurred in 13% of patients, and no treatment-related deaths were observed. Best Overall Response Rate (BORR) and Disease Control Rate (DCR) were 27 and 57%, respectively. Median overall survival was 16.2 months. Response to treatment was positively correlated with a higher tumor CD3 + infiltrate (immune score) at baseline. NRAS and BRAF mutations were less frequent in patients who experienced clinical benefit. Assessment of peripheral blood revealed that non-responders had elevated baseline levels of CXCL8 and CCL4, and a higher proportion of circulating late differentiated B cells. Pre-existing high levels of chemokines (CCL3, CCL4 and CXCL8) and advanced B cell differentiation were strongly associated with worse patient overall survival. Elevated proportions of circulating CD8 + /PD-1 + T cells during treatment were associated with worse survival. Conclusions: The combination of ipilimumab and CP was well tolerated and revealed novel characteristics associated with patients likely to benefit from treatment. A pre-existing systemic inflammatory state characterized by elevation of selected chemokines and advanced B cell differentiation, was strongly associated with poor patient outcomes, revealing potential predictive circulating biomarkers. Trial registration: Clinicaltrials.gov, NCT01676649, registered on August 29, 2012.